Livelihood Challenges of Adjacent Communities of Selected National Parks in West Africa - Emmanuel, Adebayo Adewunmi; Arowosafe, Folusade Catherine (Advances in Social Sciences Research Journal, 2017)
The livelihood challenges of communities adjacent to Kainji Lake and Mole National Parks in Nigeria and Ghana respectively were studied. This was intended to underscore the concept of Sustainable Livelihood in poverty alleviation. Survey design was employed using semi-structured questionnaire, Focus Group Discussion and Key Informant Interview to gather data from 582 residents of 20 communities adjacent to both Parks. Descriptive and inferential statistics were used for data analysis. Results obtained show that the major livelihood activities at adjacent communities of both Parks were crop and livestock farming. Some livelihood challenges encountered at the communities include destruction of crops by wild animals, reduced access to farmlands, and exclusion from use of natural resources. Chi-squared analysis also reveals a significant difference between the challenges encountered at the adjacent communities to both Parks. To reduce the adverse effects of the Parks on the communities, compensation for damages, further collaboration with NGOs to provide infrastructure, and training on alternative sources of livelihood are recommended.